Evidence for Integrin Venus Kinase Receptor 1 Alliance in the Ovary of Schistosoma mansoni Females Controlling Cell Survival - Gelmedin, Verena; Morel, Marion; Hahnel, Steffen; Cailliau, Katia; Dissous, Colette; Grevelding, Christoph G.; Justus Liebig University Giessen (My University, 2017)
Parasites of the genus Schistosoma cause schistosomiasis, a life-threatening infectious disease for humans and animals worldwide. Among the remarkable biological features of schistosomes is the differentiation of the female gonads which is controlled by pairing with the male and a prerequisite for egg production. Eggs, however, are not only important for the maintenance of the life-cycle; they also cause the pathological consequences of schistosomiasis. Part of the eggs gets trapped in host tissues such as liver and spleen and trigger inflammatory processes, finally leading to liver cirrhosis. Research activities of the last decade have indicated that different families of cellular and receptor-type kinases but also integrins contribute to the control of mitogenic activity and differentiation the female goands. In this context an unusual class of receptor tyrosine kinases (RTKs) has been identified, the venus kinase receptors (SmVKRs). By biochemical and molecular approaches we demonstrate that SmVKR1 activation can be achieved by cooperation with a signaling complex consisting of the beta integrin receptor Smß-Int1 and the bridging molecules SmILK, SmPINCH, SmNck2. Besides unravelling a novel way of SmVKR1 activation, we provide evidence that this complex controls the differentiation status of oocytes by regulating cell death-associated processes.
Keywords: ddc:630